Hybrid kerberos assisted authentication in MANETS - Dario, Kristine Marie; Roxas, Sarah Kristine; Villaraza, Jocelyn Mae. (2006)
Self-organizing interest based networks are starting to make its way to the mainstream on how mobile devices with wireless connections cooperate with each other. These networks are usually built on top of ad hoc networks, which brings us to issues regarding the security of the network. Each user should be able to identify the other users of the interest based network as well as those belonging to the same interest groups as he does. But aside from the robustness of this security system, we also have to consider the resources that will be exhausted by the system since we are dealing with mobile devices on ad hoc networks, which means limited power and limited range of connectivity. The best candidate we explored was the Kerberos Authentication system [12] which is actually a ticket based authentication system, which solves the problem of connectivity and computation as this scheme does not require the clients to be constantly connected to the authentication server. In this thesis, we designed a hybrid of the existing Kerberos Assisted Authentication in Mobile Adhoc Networks [14] for it to work with a self-organizing interest based network. As in KAMAN, clients simply have to authenticate themselves to each other, in self organizing groups, the users also have to identify users that belong to the same interest group as they do. Of course, once authentication is over, clients must also be able to make transaction with other clients securely, which brings us to our second objective which is to secure the data transmissions across the network.
Thesis (B.S. Computer Science)--University of the Philippines Diliman.
Keywords: Ad hoc networks (Computer networks); Computer networks -- Security measures; Mobile Adhoc Networks (MANETS).; Kerberos Authentication System